Optimization of switching losses and capacitor voltage ripple using model predictive control of a cascaded H-bridge multi-level StatCom - Townsend, Christopher D.; Summers, Terence J.; Vodden, John Alan; Watson, Alan James; Betz, Robert E.; Clare, Jon C. (IEEE, 2013)
This paper further develops a Model Predictive Control (MPC) scheme which is able to exploit the large number of redundant switching states available in a multi-level H-bridge StatCom (H-StatCom). The new sections of the scheme provide optimised methods to trade off the harmonic performance with converter switching losses and capacitor voltage ripple. Varying the pulse placement within the modulation scheme and modifying the heuristic model of the voltage balancing characteristics allows the MPC scheme to achieve superior performance to that of the industry standard phase shifted carrier modulation technique. The effects of capacitor voltage ripple on the lifetime of the capacitors is also investigated. It is shown that the MPC scheme can reduce capacitor voltage ripple and increase capacitor lifetime. Simulation and experimental results are presented that confirm the correct operation of the control and modulation strategies.